2020
DOI: 10.1038/s41385-019-0228-3
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microbiota drive the functional diversification of colon macrophages

Abstract: Mononuclear phagocytes are a heterogeneous population of leukocytes essential for immune homeostasis that develop tissuespecific functions due to unique transcriptional programs driven by local microenvironmental cues. Single cell RNA sequencing (scRNA-seq) of colonic myeloid cells from specific pathogen free (SPF) and germ-free (GF) C57BL/6 mice revealed extensive heterogeneity of both colon macrophages (MPs) and dendritic cells (DCs). Modeling of developmental pathways combined with inference of gene regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 76 publications
(113 reference statements)
3
69
3
Order By: Relevance
“…Our scRNA-seq data set, together with conditional mouse lines, indicated that the amino acid transporter CD98hc is in part required for the development of MHCII + macrophages as the numbers of MHCII + macrophages are reduced in the colonic lamina propria of cKO animals. One possibility is that branchedchain amino acids derived from nutritional cues, the host, or the microbiota, facilitate the differentiation of monocytes into macrophages 12,13 , whose adaptation to the gut environment depends on TGFβR signaling 24,36 , and whose numbers are reduced in germ-free animals 2,[37][38][39] . At this stage, we cannot explain the deeper molecular mechanisms why the conditional deletion of CD98hc leads to increased apoptosis in colonic macrophage progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Our scRNA-seq data set, together with conditional mouse lines, indicated that the amino acid transporter CD98hc is in part required for the development of MHCII + macrophages as the numbers of MHCII + macrophages are reduced in the colonic lamina propria of cKO animals. One possibility is that branchedchain amino acids derived from nutritional cues, the host, or the microbiota, facilitate the differentiation of monocytes into macrophages 12,13 , whose adaptation to the gut environment depends on TGFβR signaling 24,36 , and whose numbers are reduced in germ-free animals 2,[37][38][39] . At this stage, we cannot explain the deeper molecular mechanisms why the conditional deletion of CD98hc leads to increased apoptosis in colonic macrophage progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal macrophages play an important role to maintain this balance. Interestingly, the intestinal microbiota shapes and regulates the pool of intestinal macrophages as demonstrated by the fact, that germ-free mice are characterized by reduced total numbers of intestinal macrophages and reduced numbers of specific colonic macrophage populations (CD11c + CD206 int CD121b + and CD11c − CD206 hi CD121b − ) [ 32 , 37 ], underlining the important cross-talk between the gut microbiota and macrophage function.…”
Section: Function Of Intestinal Macrophages and Maintenance Of Tismentioning
confidence: 99%
“…However, the current macrophage classification has been extended recently, suggesting a much higher number of different macrophage subgroups [ 83 , 84 ]. In a very recent study, single cell RNA-sequencing of mature colonic myeloid cells from SPF and germ-free (GF) mice was performed and identified seven different colon macrophage clusters, again challenging the existence of one classically defined macrophage population in the gut under steady state conditions [ 37 ].…”
Section: Function Of Intestinal Macrophages and Maintenance Of Tismentioning
confidence: 99%
“…Host cells can be studied through in vivo and ex vivo mechanism to understand cell heterogeneity in the context of microbial influences. (F) A variety of host cells can be studied through single-cell RNA-seq (scRNA-seq) of cells from model organisms with varying degrees of microbiota alteration (Gury-BenAri et al, 2016 ; Kang et al, 2020 ). (G) Host immune cells subjected to pathogens can be sorted by cell outcomes and characterized by scRNA-seq to understand host heterogeneity in the context of pathogenic microbes (Avraham et al, 2015 ; Saliba et al, 2016 ).…”
Section: Microbiome Studies At Single-cell Resolutionmentioning
confidence: 99%
“…Single-cell analysis of host cells has provided novel insight into the role of both commensal and pathogenic microbes in modulating host physiology. One study in particular performed single-cell RNA sequencing on colon macrophages of germ-free (GF) and specific pathogen-free (SPF) mice (Kang et al, 2020 ). When comparing all clusters of colon macrophages from SPF mice to GF, the SPF macrophages were found to have an increase in expression of genes associated with immune defense, antigen presentation, and oxidative phosphorylation.…”
Section: Single-cell Studies Of Host Heterogeneity In the Context Of mentioning
confidence: 99%